1995
DOI: 10.1073/pnas.92.23.10604
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, regulation, and DNA-binding properties of three Drosophila nuclear hormone receptor superfamily members.

Abstract: We have designed a rapid cloning and screening strategy to identify new members of the nuclear hormone receptor superfamily that are expressed during the onset of Drosophila metamorphosis. Using In an effort to understand the molecular mechanisms of steroid hormone action, we have focused on the role of 20-hydroxyecdysone (20E) in directing the metamorphosis of the fruit fly Drosophila melanogaster. A high-titer 20E pulse at the end of third-instar larval development triggers puparium formation, followed 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 39 publications
2
79
1
Order By: Relevance
“…NR4As bind to the NBRE (NGFI-B response element), through which NR4A2 regulates the mammalian TH promoter (Maxwell and Muscat, 2006). HR38 is the single Drosophila ortholog of the mammalian NR4A family and has been shown to bind to the NBRE (Baker et al, 2003;Fisk and Thummel, 1995). Consistent with this, it has recently been reported that HR38 binds to the NBRE-like sequence upstream of the Ddc gene and that ectopic expression of HR38 influences expression of Ddc in a tissue-dependent manner (Davis et al, 2007b).…”
Section: Hr38 Is Required For P38-dependent Melanizationsupporting
confidence: 50%
“…NR4As bind to the NBRE (NGFI-B response element), through which NR4A2 regulates the mammalian TH promoter (Maxwell and Muscat, 2006). HR38 is the single Drosophila ortholog of the mammalian NR4A family and has been shown to bind to the NBRE (Baker et al, 2003;Fisk and Thummel, 1995). Consistent with this, it has recently been reported that HR38 binds to the NBRE-like sequence upstream of the Ddc gene and that ectopic expression of HR38 influences expression of Ddc in a tissue-dependent manner (Davis et al, 2007b).…”
Section: Hr38 Is Required For P38-dependent Melanizationsupporting
confidence: 50%
“…Hence, if regulatory factors other than the EcR/USP heterodimer are involved positively in the ecdysteroid response mediated by the DR3G element, they remain to be identified. On the other hand, it has been recently reported that the Drosophila nuclear receptor Svp (78) and the newly identified orphan receptor XR78E/F-DHR78 (18,79) may inhibit ecdysone signaling pathways. These receptors bind preferentially to a DR1 element but are also able to bind to a DR3 element.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, their misexpression produces slight reductions in the sensilla counts, indicating that these genes may also regulate ORN differentiation. The functions of Ches-1-like, and Hnf4 are unknown (Fisk and Thummel, 1995;Mazet et al, 2003). Although Hnf4 expression leads to a reduction in the number of trichoid sensilla, the distinct enlargement of the glomeruli indicates that Hnf4 may also have a separate role in glomerular development.…”
Section: Genes Encoding Transcription Factors and Transcription Factomentioning
confidence: 98%